Early determinants of attention and hyperactivity problems in adolescents: the 11-year follow-up of the 1993 Pelotas (Brazil) birth cohort study Determinantes precoces de problemas de atenção e hiperatividade na adolescência: a visita de 11 anos da coorte de nascimentos de Pelotas, Rio Grande do Sul, Brasil, 1993 - Luciana Anselmi; Ana M. B. Menezes; Fernando C. Barros; Pedro C. Hallal; Cora Luiza Araújo; Marlos R. Domingues; Luis A. Rohde (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2010)
The aim of this study was to assess early determinants of attention and hyperactivity problems in adolescents. In 1993, all hospital births in the city of Pelotas, Rio Grande do Sul State, Brazil, were monitored and mothers were interviewed (N = 5,249). At 11 years of age, 4,423 mothers answered the Strengths and Difficulties Questionnaire (SDQ) in order to evaluate attention and hyperactivity problems in the adolescents. Crude and adjusted prevalence ratios were calculated using Poisson regression. Prevalence of attention and hyperactivity problems was 19.9%. Factors associated with the outcome in the adjusted analysis were: male gender, low family income, smoking during pregnancy, minor psychiatric disorders in the mother, and history of child's behavioral/emotional problems at four years of age. Early life events impacted attention and hyperactivity problems in adolescence. Risk factors for attention and hyperactivity problems found in this study were similar to those reported in other cultures. O objetivo deste trabalho foi estudar determinantes precoces dos problemas de atenção e hiperatividade em adolescentes. Em 1993, os nascimentos foram recrutados e as mães entrevistadas (n = 5.249). Aos 11 anos, 4.423 mães responderam ao Strengths and Difficulties Questionnaire (SDQ) para avaliar problemas de atenção e hiperatividade nos adolescentes. Variáveis socioeconômicas, demográficas, biológicas e psicológicas foram investigadas como prováveis fatores de risco. Razões de prevalência brutas e ajustadas foram calculadas com regressão de Poisson. A prevalência de problemas de atenção e hiperatividade foi 19,9%. Sexo masculino, baixa renda familiar, tabagismo materno na gestação, transtornos psiquiátricos maternos e problemas de comportamento/emocionais do adolescente aos quatro anos permaneceram associados na análise ajustada. Eventos do início da vida influenciaram os problemas de atenção e hiperatividade na adolescência. Os fatores de risco para problemas de atenção e hiperatividade foram similares aos encontrados em diferentes culturas.